THE PROFILE OF THE TOURISTS WHO CHOOSE ALBA COUNTY AS A TOURIST DESTINATION - MUNTEAN, Andreea; MOISĂ, Claudia (Annales Universitatis Apulensis Series Oeconomica, 2014)
The tourism demand and the choice of destinations are strongly influenced by a number of factors among which: the destination’s accessibility, the natural and anthropic environment, the forms of entertainment and animation provided by each area, the local hospitality etc. In order to outline the profile of the tourists who choose to spend their holiday in Alba County, we have conducted a survey among people who were tourists during September 2013 - December 2013 in the 10 micro-regions of the county. Knowing the potential clients’ expectations, one can create tourism products tailored to the needs and wants of individual travellers or groups of tourists interested in Alba. Or, Alba is placed to become a major tourist destination on the domestic and international market.